Ecotoxicity of water-soluble lectin from Moringa oleifera seeds to zebrafish (Danio rerio) embryos and larvae. (October 2017) - de Santana Silva, Livia Lais; Alves, Romulo Nepomuceno; de Paulo, Driele Ventura; da Silva, José Dayvid Ferreira; de Oliveira, Ana Patrícia Silva; Coelho, Luana Cassandra Breitenbach Barroso; Navarro, Daniela Maria do Amaral Ferraz; Napoleão, Thiago Henrique; do Amaral, Ian Porto Gurgel; de Carvalho, Paulo Sérgio Martins; Paiva, Patrícia Maria Guedes
Abstract: The evaluation of ecotoxicity of mosquito larvicidal agents (such as the water-soluble lectin from Moringa oleifera seeds, WSMoL) is an essential step to establish the guidelines for their use. In this sense, this work evaluated the toxicity of WSMoL to Danio rerio embryos and larvae. Embryos were exposed to waterborne WSMoL (0.0125–0.2 mg mL −1 ) for 96 h and lethal and sub-lethal effects were observed every 24 h. In the bioassays with larvae, the individuals were exposed to the WSMoL (0.025–0.2 mg mL −1 ), mortality was recorded daily, and larval swimming velocities were analyzed after 72 h and 168 h of exposure. Additionally, acetylcholinesterase (AChE) activity of larvae was determined after 168 h of exposure. WSMoL LC50 values to embryos were 0.190, 0.133 and 0.049 mg mL −1 after 48, 72 and 96 h, respectively. No toxic endpoint was observed after exposure for 24 h. In addition, hatching was delayed and larval length at 96 h was reduced compared to the control. WSMoL LC50 to larvae were 0.21 and 0.135 mg mL −1, after 24 h and 96 h, respectively. Larvae exposed to 0.1 and 0.2 mg mL −1 showed a decrease in swimming speed and a significant reduction in AChE activity. In conclusion, WSMoL at waterborne concentrations needed for its use as a larvicide to A. aegypti causes lethal and sublethal effects to zebrafish embryos and larvae. Therefore, its use in waterbodies where there are non-target organisms is not recommended. Highlights: Zebrafish embryos and larvae were exposed to the water soluble M. oleifera lectin (WSMoL). WSMoL concentrations needed to control A. aegypti larvae are toxic to zebrafish. WSMoL caused D. rerio embryo lethality, hatch delay and growth reduction. WSMoL caused D. rerio larval lethality, acetylcholinesterase inhibition and hypoactivity. WSMoL use in aquatic ecosystems is not recommended.